Therapeutic vulnerabilities in the DNA damage response for the treatment of ATRX mutant neuroblastoma - Sally L George; Federica Lorenzi; David King; Sabine Hartlieb; James Campbell; Helen Pemberton; Umut H Toprak; Karen Barker; Jennifer Tall; Barbara Martins da Costa; Marlinde L van den Boogaard; M Emmy M Dolman; et al. (EBioMedicine, 2020)
Background: In neuroblastoma, genetic alterations in ATRX, define a distinct poor outcome patient subgroup. Despite the need for new therapies, there is a lack of available models and a dearth of pre-clinical research. Methods: To evaluate the impact of ATRX loss of function (LoF) in neuroblastoma, we utilized CRISPR-Cas9 gene editing to generate neuroblastoma cell lines isogenic for ATRX. We used these and other models to identify therapeutically exploitable synthetic lethal vulnerabilities associated with ATRX LoF. Findings: In isogenic cell lines, we found that ATRX inactivation results in increased DNA damage, homologous recombination repair (HRR) defects and impaired replication fork processivity. In keeping with this, high-throughput compound screening showed selective sensitivity in ATRX mutant cells to multiple PARP inhibitors and the ATM inhibitor KU60019. ATRX mutant cells also showed selective sensitivity to the DNA damaging agents, sapacitabine and irinotecan. HRR deficiency was also seen in the ATRX deleted CHLA-90 cell line, and significant sensitivity demonstrated to olaparib/irinotecan combination therapy in all ATRX LoF models. In-vivo sensitivity to olaparib/irinotecan was seen in ATRX mutant but not wild-type xenografts. Finally, sustained responses to olaparib/irinotecan therapy were seen in an ATRX deleted neuroblastoma patient derived xenograft. Interpretation: ATRX LoF results in specific DNA damage repair defects that can be therapeutically exploited. In ATRX LoF models, preclinical sensitivity is demonstrated to olaparib and irinotecan, a combination that can be rapidly translated into the clinic. Funding: This work was supported by Christopher's Smile, Neuroblastoma UK, Cancer Research UK, and the Royal Marsden Hospital NIHR BRC.